The transcription factor Pax6 contributes to the induction of GLT‐1 expression in astrocytes through an interaction with a distal enhancer element. Issue 2 (24th November 2015) - Ghosh, Mausam; Lane, Meredith; Krizman, Elizabeth; Sattler, Rita; Rothstein, Jeffrey D.; Robinson, Michael B.
Abstract: The Na + ‐dependent glutamate transporter GLT‐1 (EAAT2) shows selective expression in astrocytes, and neurons induce the expression of GLT‐1 in astrocytes. In an unpublished analysis of GLT‐1 promoter reporter mice, we identified an evolutionarily conserved domain of 467 nucleotides ~ 8 kb upstream of the GLT‐1 translation start site that is required for astrocytic expression. Using in silico approaches, we identified Pax6 as a transcription factor that could contribute to the control of GLT‐1 expression by binding within this region. We demonstrated the expression of Pax6 protein in astrocytes in vivo . Lentiviral transduction of astrocytes with exogenous Pax6 increased the expression of enhanced green fluorescent protein (eGFP) in astrocytes prepared from transgenic mice that use a bacterial artificial chromosome containing a large genomic region surrounding the GLT‐1 gene to control expression of eGFP. It also increased GLT‐1 protein and GLT‐1‐mediated uptake, whereas there was no effect on the levels of the other astroglial glutamate transporter, glutamate aspartate transporter (GLAST). Transduction of astrocytes with an shRNA directed against Pax6 reduced neuron‐dependent induction of GLT‐1 or eGFP. Finally, we confirmed Pax6 interaction with the predicted DNA‐binding site in electrophoretic mobility assays and chromatin immunoprecipitation (ChIP). Together, these studies show that Pax6 contributes to the regulation of GLT‐1 through an interaction with these distal elements and identify a novel role of Pax6 in astrocyte biology. The astroglial glutamate transporter GLT‐1 shows selective expression in astrocytes and its expression can be induced by neurons. In this study, we demonstrate that Pax6 is expressed in astrocytes and binds to the GLT‐1 promoter in vitro and in vivo . Exogenous expression of Pax6 increases GLT‐1 and enhanced green fluorescent protein (eGFP) expression in astrocytes from a transgenic mouse line that uses the GLT‐1 gene to drive eGFP expression, and an shRNA directed against Pax6 attenuates neuron‐dependent induction of GLT‐1/eGFP. We therefore conclude that Pax6 contributes to the neuron‐dependent induction of GLT‐1. Abstract : The astroglial glutamate transporter GLT‐1 shows selective expression in astrocytes and its expression can be induced by neurons. In this study, we demonstrate that Pax6 is expressed in astrocytes and binds to the GLT‐1 promoter in vitro and in vivo . Exogenous expression of Pax6 increases GLT‐1 and enhanced green fluorescent protein (eGFP) expression in astrocytes from a transgenic mouse line that uses the GLT‐1 gene to drive eGFP expression, and an shRNA directed against Pax6 attenuates neuron‐dependent induction of GLT‐1/eGFP. We therefore conclude that Pax6 contributes to the neuron‐dependent induction of GLT‐1.